Did Chinese children with imaginary companions attribute more agencies to non-human items: Evidences from behavioral cues and appearance characteristics - Qiyi, Lin; Ruiyi, Zhang; Yiwen, Zhang; Nan, Zhou (Frontiers in Psychology, 2022)
Previous studies have focused on the relationship between imaginary companions (ICs) and children’s social developments. As far as we know, few studies have focused on the relationship between ICs and children’s agency attributions. This study aimed to explore the potential differences in agency attributions between children with and without ICs, children with egalitarian IC relationships and hierarchical IC relationships. Children’s agency attributions were measured by two experiments. One was based on behavioral cues (Random animations/ToM animations) and the other was based on appearance characteristics (ball/doll). The results revealed that children with ICs attributed more cognitive properties to Random and ToM animations than children without ICs. Compared with children without ICs, children with ICs attributed marginally more biological properties to a ball and more psychological properties to a ball and a doll. However, children with egalitarian and hierarchical IC relationships did not differ in their agency attributions. The results suggest that children with ICs are more likely to attribute agencies to non-human items with behavioral cues or appearance characteristics than children without ICs. Compared with child-IC relationship qualities, IC status may be more related to children’s agency attributions. However, only a correlation between IC status and children’s agency attributions was found in this study and it is interesting for future researchers to investigate the potential causal directions between children’s IC status and their agency attributions. If one of the causal directions or both the causal directions exist, future researchers can further explore the underlying mechanism.